2016
DOI: 10.1016/j.cej.2016.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Scalable processing of thermoplastic polyurethane nanocomposites toughened with nanocellulose

Abstract: The production of strong and elastic polyurethane nanocomposites toughened with nanocellulose and their widespread application in many engineering fields are currently limited by poor processability via classical industrial processing methods and/or the usage of large amount of solvents. In this report, we demonstrate a scalable, organic solvent-free incorporation of nanocellulose into thermoplastic polyurethane (TPU) and a remarkable reinforcement without compromising elastic properties. The nanocomposites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 60 publications
0
40
1
Order By: Relevance
“…Many efforts have been devoted to strengthening and toughening TPU via incorporation of fillers [5,6,7,8,9] and in-situ synthetic methods [10]. Synthesizing TPU with high performance refers to molecular structure and condensed state design that consequentially controls network, soft and hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to strengthening and toughening TPU via incorporation of fillers [5,6,7,8,9] and in-situ synthetic methods [10]. Synthesizing TPU with high performance refers to molecular structure and condensed state design that consequentially controls network, soft and hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the improved phase-mixing and interfacial adhesion between nanocrystal and polymer matrix at an optimum NCO/OH ratio, which might cause local resistance for segmental movements of polymer chains and consequently decrease the deformation. [7,58] However, at an off-ratio, the microphase separation might be affected due to poor phase-mixing and causing slippage for creep behavior. [7,59]…”
Section: Creep Resistancementioning
confidence: 99%
“…[7,58] However, at an off-ratio, the microphase separation might be affected due to poor phase-mixing and causing slippage for creep behavior. [7,59]…”
Section: Creep Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have shown the ability of nanocellulose to form aerogels, which are low-density foams derived from a gel-state material (Jin et al 2004). Additionally, many recent studies have investigated the possibility of improving polyurethane foam properties through the addition of nanocellulose (Auad et al 2007;Wik et al 2011;Faruk et al 2013;Amin et al 2016;Lee et al 2016;Ivdre et al 2016;Zhou et al 2016).…”
Section: Introductionmentioning
confidence: 99%